The News in Album Studies (Two Case Reviews) - Ūsaitytė, Jurgita (Tautosakos darbai, 2016)
The author reviews two publications in album studies. The stimulus to write this review was primarily the personal impression induced by the scope of scientific and cultural information combined with professional one, and equally attractive way of its presentation. The two books in question address different readership and apply different methods, yet they deal with the same cultural phenomenon and in a certain way continue and supplement each other. The first subject of the review is the beautiful, amply illustrated publication of the Wroblewski Library of the Lithuanian Academy of Sciences, entitled The Garden of Remembrances (2016) and consisting of two separate parts. Reda Griškaitė, the author of the first part called „Essays in Album Studies“, gradually reveals the stages of shaping the album canon, the reasons and ways of its change, the meaning that individual inscriptions or drawings had to the albums’ owners and their contemporaries. She discusses the close connections existing between the contents of these “books of friends” and the forms of the cultural life, the structure of the social relations, and the historical situation of the past epochs. The essay presents concise yet very informative cultural study, incorporating special knowledge from various disciplines, including literature studies, history, art, music, botany etc. Each fragment of this essay deals with separate feature of the album contents and aesthetics. To introduce the history and development of the album genre, the author of the essay analyses fifty albums stored at the Wroblewski Library (the first inscription in them dating as early as 1609, while the last coming from 1973). The author also discusses at least thirty unique manuscripts, preserved at other libraries both in Lithuania and abroad, or in private keeping. The second part of the book presents the catalogue of the albums stored at the Wroblewski Library, compiled by the book researcher Rima Cicėnienė following the international practice in this field. This catalogue is the first register of album amicorum accumulated in a single institution of the Lithuanian cultural heritage.Unlike the previously reviewed publication, focusing mostly on the old, classic albums, the second book discussed in this review deals with the late kind of albums that thrived in the 20th century. This is the monograph The Tradition of Autograph Albums in the Culture of Latvian Schoolchildren (2013) by the Latvian folklorist Baiba Krogzeme-Mosgorda. Using the contextual method of analysis, this author focuses on the social environment of the albums, which she highlights by discussing the influences that institutions (like school), family, community, various subcultures and other social factors (including age groups, gender, and social status) had on this kind of written culture, its contents and expression. Among the schoolchildren, the albums played not only an important socializing role. The analysis of the textual repertoire and decorations used in them enables recognizing the schoolchildren’s albums of remembrances as an educational activity that also enhances creativity
Keywords: -